Genetic profile, risk factors and therapeutic approach of desmoid tumors in familial adenomatous polyposis - Freitas,Ana Catarina Ribeiro (2017)
ABSTRACT Introduction: Desmoid tumors are the main extraintestinal manifestation of FAP, presenting high morbidity and mortality. It is a neoplasia without metastasis capacity, but with infiltrative growth and with a high rate of recurrence. In familial forms, these tumors are associated with a germinal mutation in the APC gene, with a genotype-phenotype correlation influenced by other risk factors. Materials and methods: A review of articles published since the year 2000 in Portuguese, English or Spanish on desmoid tumors in patients with FAP was carried out. A total of 49 publications were included. Results: The site of the mutation in the APC gene is related to the severity of FAP and to the frequency of desmoid tumor. Mutations located distally to codon 1309 are associated with a more attenuated polyposis, but with higher frequency of desmoid tumors. Clinically, these tumors may or may not be symptomatic, depending on their size and location. In their treatment, priority should be given to medical therapy, especially in intra-abdominal tumors, with surgery being the last option if there are no other complications. Discussion: These tumors are associated with certain risk factors: genetic (mutation site), hormonal (estrogenic environment) and physical (surgical trauma) ones. In young women, a later prophylactic colectomy is suggested. Moreover, the laparoscopic approach to prophylactic surgery seems to be an option that reduces surgical trauma and consequently the appearance of desmoid tumors. Conclusion: The step-up medical approach has been shown to be valid in the treatment of intra-abdominal desmoid tumors, and medical treatment should be the first therapeutic option.